Factors Related to the Incidence of Dysphagia in Patients Using Tracheal Cannula at Dr. Mohammad Hoesin General Hospital Palembang - Puspa Zuleika; Mariance; Erial Bahar (HM Publisher, 2022)
Background: The need for tracheostomy increases during the coronavirus diseases 2019 (COVID-19) pandemic. However, some studies suggest that tracheostomy causes dysphagia which can lead to other health problems such as pneumonia, choking, weight loss, malnutrition, and dehydration with serious side effects. This study aims to determine the factors associated with the incidence of dysphagia in patients using a tracheal cannula. Methods: This study is an observational study using a cross-sectional design. Data collection was carried out using medical record data on 58 patients who used a tracheal cannula recorded in the medical record data for the FEES examination at Dr. Mohammad Hoesin General Hospital Palembang from January 2019 to September 2021. The data were analyzed by descriptive statistics, chi-square, and multiple logistic regression. Results: Of 58 patients who used a tracheal cannula, it was found that 75.9% had dysphagia. The results of the comparison test showed that the factors associated with the incidence of dysphagia were gender (p=0.001), nutritional status (p=0.013), incision location (p=0.043), and primary disease (p=0.021). Factors that were not associated with the incidence of dysphagia were age (p=0.933), tracheostomy indication (p=0.741), and the type of tracheal cannula (p=1,000). Patients are male, with low and high tracheal cannula incision locations, and have a primary neurological disease. The probability or chance of dysphagia is 79.8%. Conclusion: Tracheostomy can cause dysphagia which is influenced by gender, location of tracheal cannula incision, and primary disease.